2009
DOI: 10.1097/shk.0b013e318180ffe9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anticoagulants and the Role of Thrombin on Neutrophil-Endothelial Cell Interactions in Septic Shock

Abstract: To examine the effects of anticoagulants and the role of thrombin on neutrophil-platelet-endothelial cell interactions in septic shock. Controlled experiments using phase-contrast microscopy to study neutrophil, platelet, and endothelial cell interactions in flowing cell suspensions under simulated physiologic conditions. University research laboratory. Adult patients with septic shock and normal volunteers. Microslides were coated with human umbilical vein endothelial cells. Neutrophils and platelets removed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In vitro experiment was performed in a coagulation factor-free medium, and the effect of argatroban could not be expected. Tsen et al [ 26 ] performed the in vitro experiment by using plasma and reported that both UFH and argatroban significantly decreased neutrophil adhesion and platelet-neutrophil aggregation. They concluded that UFH and argatroban decrease sepsis-induced neutrophil-endothelial cell interactions by inhibiting thrombin activity.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiment was performed in a coagulation factor-free medium, and the effect of argatroban could not be expected. Tsen et al [ 26 ] performed the in vitro experiment by using plasma and reported that both UFH and argatroban significantly decreased neutrophil adhesion and platelet-neutrophil aggregation. They concluded that UFH and argatroban decrease sepsis-induced neutrophil-endothelial cell interactions by inhibiting thrombin activity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, thrombin, one of the key participants in the coagulation cascade, can also be involved in the control of neutrophil migration. Previously, Tsen et al showed that a range of thrombin-specific inhibitors significantly decreased the adhesion of neutrophils to endothelial cells and increased their rolling velocity [89], thereby diminishing the transmigration of neutrophils from blood vessels into inflamed sites. Thus, we supposed that the anti-inflammatory properties of compound 3d could be due to its inhibitory effect on the activity of MMP9, neutrophil elastase, and thrombin, which can lead to the dysregulation of optimal chemokine processing and the generation of that chemotactic gradient that guides neutrophils into an inflamed site, as well as the suppression of transendothelial neutrophil migration.…”
Section: Figurementioning
confidence: 99%
“…APC treatment is still recommended for the therapy of severe sepsis and septic shock (3,4). Because of the central role of the coagulation cascade in sepsis, other anticoagulants were studied in clinical and experimental sepsis, including heparin, antithrombin (ATIII), tissue factor pathway inhibitor (TFPI), and hirudin (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%